THE EFFECTS OF HOMOGENEOUS AND HETEROGENEOUS PUSHED OUTPUT INSTRUCTIONS ON SPEAKING COMPLEXITY - Parviz Ghasedi; Habibollah Mashhady; Farideh Okati (University of Kuningan, 2017)
This study was set out to investigate the efficacy of homogeneous and heterogeneous pushed output based instruction on upper-intermediate EFL learner’ speaking complexity. To do so, 41 (17 males and 24 females) EFL learners were selected from University of Zabol based on the results of OPT. Then, they were put in control and experimental groups based on the predetermined criteria. Retelling and decision making tasks were used in the treatments of experimental groups while control group received placebo during 15 sessions, twice a week. Public versions of IELTS speaking test were used as pre/post-test. The results of Independent sample t-test indicated that experimental groups outperformed control group. On the other hand, statistical analyses showed no significant differences between male and female speech complexity. To sum up, the findings demonstrated the fruitful effects of collaborative pushed output activities on speaking sub-skills. Likewise, the results suggested the implementation of similar strategies in the development of male and female speaking dimensions. Based on the findings, it can be claimed that teacher preparation programs should put teaching speaking on their list of priorities and provide courses on effective strategies for the development of speaking dimensions through implementing the main tenants of pushed output hypothesis.Keywords: homogeneous, heterogeneous, complexity, speaking, pushed output